Dialectics of the National-Peculiar and Universal in the Development of Family and Household Traditions (Eurasian Journal of Humanities and Social Sciences, 2022)
The common goal and task of the development of the spiritual sphere, as well as the sphere of public consciousness of any civilized society, is the development of creative abilities of the individual, without which it seems unthinkable to increase the overall level of development of peoples, recognition by the international community as equal members of the modern commonwealth of democratic states.